1998
DOI: 10.1021/es980702c
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Natural, Commercial, and Modified Calcium-Based Sorbents as H2S Removal Agents at High Temperatures

Abstract: Coal gas desulfurization is one of the most important gas cleaning steps previous to its use in a gas turbine in integrated gasification combined cycle (IGCC) systems. In this work, 12 different calcium based materials, both natural, commercial and modified with several additives, were tested in a drop tube reactor as potential H2S removal agents at high temperatures and reducing conditions. Three limestones and a dolomite were selected by their different natures and reactivities. The commercial products used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It can also be used as a fuel tracer to characterize the chamber of a combustion device, because it exhibits a strong fluorescence signal that can be monitored through the laser-induced fluorescence technique (see, for example, refs ). Acetone can also be generated when using sorbents to control sulfur emissions in high-temperature combustion and gasification processes. , Sorbents that can be used include calcium acetate and calcium magnesium acetate, each of which emit acetone, which further reacts under combustion conditions . In addition, acetone may play an important role in the chemistry of the atmosphere, because it is one of the most abundant oxygenated organic compounds, produced either through the radical oxidation of hydrocarbons under atmospheric conditions or through uncontrolled burning fires …”
Section: Introductionmentioning
confidence: 99%
“…It can also be used as a fuel tracer to characterize the chamber of a combustion device, because it exhibits a strong fluorescence signal that can be monitored through the laser-induced fluorescence technique (see, for example, refs ). Acetone can also be generated when using sorbents to control sulfur emissions in high-temperature combustion and gasification processes. , Sorbents that can be used include calcium acetate and calcium magnesium acetate, each of which emit acetone, which further reacts under combustion conditions . In addition, acetone may play an important role in the chemistry of the atmosphere, because it is one of the most abundant oxygenated organic compounds, produced either through the radical oxidation of hydrocarbons under atmospheric conditions or through uncontrolled burning fires …”
Section: Introductionmentioning
confidence: 99%
“…H 2 S partly dissolves in water to form a weak acid and CaO would readily attract a water molecule to convert to a more stable form of calcium hydroxide (CaOH) 2 . Yet, the chances of additional reaction between CaOH and H 2 S to form CaS are low as this reaction could only happen at high temperature, i.e., above 900 • C [51]. chemical reaction increases with increasing RH [41].…”
Section: Effect Of Reaction Temperature and Humiditymentioning
confidence: 99%
“…The organic acetate content of the CMA has been shown, in these recent studies, to behave as a conventional fuel. Other studies have demonstrated the ability of carboxylic salts of calcium to remove SO 2 and H 2 S from combustion or gasification product gases at greater efficiency than limestone or dolomite sorbents. Other alternative fuels, such as biomass, have been demonstrated to perform well as reburn fuels for NO x control .…”
Section: Introductionmentioning
confidence: 99%